1991
DOI: 10.1159/000288526
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy in Patients with Poorly Controlled Type 1 (Insulin-Dependent) Diabetes

Abstract: We studied a group of 9 poorly controlled type 1 diabetic patients who were referred to the metabolic ward for a 10-day intensive patient education and treatment period and followed thereafter for 1 year. The psychodynamically and phase-specifically oriented intensive psychotherapy was prescribed. In terms of mental coping ability assessed by an index constituting the attitude towards diabetes, the family support and the expectations from the psychotherapy, the final outcome was classified as good or moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…In adults with poorly controlled diabetes, three studies were found reporting the effects of psychological counselling. Viinamaeki and colleagues [92] studied a group of nine poorly controlled Type 1 diabetes patients (five men, four women, mean age 29 ± 12 years), who were referred to the metabolic ward for a 10-day intensive patient education and treatment period, and followed thereafter for 1 year. No significant improvement in glycaemic control was reached in these patients, but seven out of the nine were found to have 'moderate to good' outcome in terms of better mental coping ability.…”
Section: Self-destructive Behavioursmentioning
confidence: 99%
“…In adults with poorly controlled diabetes, three studies were found reporting the effects of psychological counselling. Viinamaeki and colleagues [92] studied a group of nine poorly controlled Type 1 diabetes patients (five men, four women, mean age 29 ± 12 years), who were referred to the metabolic ward for a 10-day intensive patient education and treatment period, and followed thereafter for 1 year. No significant improvement in glycaemic control was reached in these patients, but seven out of the nine were found to have 'moderate to good' outcome in terms of better mental coping ability.…”
Section: Self-destructive Behavioursmentioning
confidence: 99%
“…Approximately 30% of patients with Type 1 diabetes are in persistent poor glycaemic control [1–3], largely due to difficulties in coping with the demands of self‐regulation. Psychological interventions to improve glycaemic control in adults have been targeted at patients with specific psychological disorders [4–6]. However, for patients without psychological comorbidity, no protocol‐driven coping‐oriented interventions are available.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that satisfaction with the doctor consultation improves glycemic control [43]. Experiences from psychotherapy with poorly controlled Type 1 diabetic patients also give support to the importance of positive transference as providing grounds for good metabolic control in diabetes [44].…”
Section: Discussionmentioning
confidence: 96%